Understanding Moral Ethics and Its Relationship with Students’ Moral Conduct in Social Media Use - Listianata, Refaldi; Putra, Satria Nugraha; Renata , Nadia; Syafa'a, Najwa Naila; Khamim, M. (Unisia, 2025)
This study examines students’ understanding of moral ethics and its relationship with moral conduct in social media use among first-year students of the Faculty of Engineering, Universitas Brawijaya. In the context of the increasing intensity of social media use among university students, this research aims to analyze how moral–ethical understanding shapes responsible, respectful, and ethical behavior in digital interactions. Using a quantitative correlational design, data were collected through an online questionnaire employing a Likert-scale instrument that measured two main variables: moral ethics understanding and moral conduct in social media use. The respondents consisted of 68 first-year engineering students selected through purposive sampling across several departments. The findings indicate a high level of moral ethics understanding among respondents, reflected in a strong tendency to agree with ethical principles such as respectful communication, protection of others’ privacy, responsibility for digital actions, and rejection of hoaxes, hate speech, and offensive content. Overall, positive responses dominated the data, suggesting that most students demonstrate commendable moral conduct in social media environments. The results further show a positive relationship between moral ethics understanding and moral behavior in social media use, indicating that students with higher ethical awareness tend to exhibit better moral conduct online. These findings underline the importance of moral and ethical education in higher education, particularly in preparing students to navigate digital spaces responsibly. The study concludes that strengthening moral ethics education can contribute to healthier and more ethical social media practices among university students, with implications for curriculum development and character education in academic institutions.